Deutscher Orden und Preussen. Livland - Wagner, P.; Mettig, Constantin; Mettig, C. (My University, 1882)
Izvilkums no "Historische Jahresberichte. II. 1882."
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Vācu ordenis; Teitoņu ordenis; Prūsijas vēsture; Livonijas vēsture; Baltijas vēsture; German Order; Teutonic Order; Prussia - history; Livonia - history; Baltic history; Deutscher Orden; Preussen - Geschichte; Livländische Geschichte; Baltische Geschichte